2021
DOI: 10.1007/s42991-021-00167-6
|View full text |Cite
|
Sign up to set email alerts
|

Eyes, ears, or nose? Comparison of three non-invasive methods to survey wolf recolonisation

Abstract: The development and use of cost-effective and appropriate survey methods to assess species distribution and to monitor range expansion and contraction of wild populations is crucial due to the limited financial resources for conservation. Of particular importance, yet little studied, is the ability to collect information before a wild population is well established, i.e. at the early stages of recolonisation. During 2018 and 2019, we used camera traps, audio recorders, and scat detection dogs simultaneously to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…CDD efficacy should be evaluated during training and testing rather than waiting until operational searches to assess performance, however, many published studies simply investigate whether CDD can discriminate the target odour in a simple controlled trial and do not progress to testing the CDD in a field environment under operational conditions. Indeed, of the 67 studies examined in this review, Of studies assessing performance in the field, scat surveys of mammals are the most prevalent with precision rates of between 30.8% to 100% (Beckmann, 2006;Clare et al, 2015;Cozzi et al,…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…CDD efficacy should be evaluated during training and testing rather than waiting until operational searches to assess performance, however, many published studies simply investigate whether CDD can discriminate the target odour in a simple controlled trial and do not progress to testing the CDD in a field environment under operational conditions. Indeed, of the 67 studies examined in this review, Of studies assessing performance in the field, scat surveys of mammals are the most prevalent with precision rates of between 30.8% to 100% (Beckmann, 2006;Clare et al, 2015;Cozzi et al,…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Indeed, modern guidelines for conservation methods, such as 'What Works in Conservation 2021' by Sutherland et al (2021) along with governmental protocols for target species searches (Thompson et al, 2020), do not include CDD despite their widespread use, which may be indicative of the concerns around their efficacy. Given that conservation suffers from underfunding (Cozzi et al, 2021;Cristescu et al, 2020), the tool used for a project must be worth the cost.…”
Section: Dogs Began Working In Conservation In the 1890s In Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them showed that different applied methods could lead to similar outcomes, suggesting that the sampling protocol choice should be based on the available resources and ecological features of the study area [ 15 , 16 ]. Conversely, other studies found that only the combination of different methods could ensure reliable results [ 17 , 18 , 19 , 20 ]. Several research projects have been carried out so far to investigate the population ecology of the Italian wolf ( C. l. italicus ) and possible threats to its conservation status, mainly in the central-northern Apennines, through WH [ 21 , 22 ], CT [ 13 , 23 ] and NGS [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 97%